Insights into the influence of waste ceramic tiles powder on cement hydration and microstructure from electrochemical impedance spectroscopy - Wang, Shudong; Huang, Qiang; Feng, Yu; Wu, Lipeng (Frontiers in Materials, 2026)
To reduce carbon emissions from cement production and achieve the resource utilization of ceramic wastes, this work investigated the effects of waste ceramic tiles powder (WCTP), used as a mineral admixture at replacement levels of 0%–50% by mass, on the course of hydration, microstructural evolution, and compressive strength of cement-based materials. The research method centered on electrochemical impedance spectroscopy (EIS), and was complemented by uniaxial compression tests, mercury intrusion porosimetry analysis, and microstructural observation for cross-validation. The results show that the incorporation of WCTP delays the early-age hydration process, leading to a substantial decrease in 3-day compressive strength with increasing replacement rate; at a 50% replacement level, the 3-day strength is only 35% of that of the Portland cement reference sample. The addition of WCTP coarsens the pore structure of cement-based materials at early ages. Nevertheless, in the later stages of hydration (at 56 days), the pozzolanic effect of the WCTP gradually becomes prominent, resulting in a denser microstructure. Consequently, the compressive strength of specimen with a 20% replacement rate reaches 95% of the strength of the reference sample. EIS analysis reveals that during the early period of hydration (before 7 days), the incorporation of WCTP reduces both the bulk resistance and its growth rate. In the later stage, however, the bulk resistance growth rate surpasses that of Portland cement specimen. The pore solution resistance decreases with increasing WCTP content, particularly at early ages. At later ages, the differences in pore solution resistance among hardened pastes with 20%–50% WCTP replacement gradually narrow, indicating that the differences in porosity within the hardened pastes tend to decrease. Furthermore, EIS analysis shows that the charge transfer resistance is positively correlated with compressive strength. These findings confirm that bulk resistance, pore solution resistance, and charge transfer resistance are key electrochemical indicators suitable for the non-destructive monitoring of hydration processes and strength gain in cementitious materials incorporating WCTP.